Interdisciplinary mentoring in science strategies for success - Olivero, Ofelia A. (Amsterdam Elsevier/AP, 2014)
Interdisciplinary Mentoring in Science: Strategies for Success is a practical and engaging resource on interdisciplinary mentoring in all fields of science. This book outlines what successful mentoring is, what it is not and how these important concepts relate to scientists today. Chapters include real-world examples, tips, and interviews and content is backed by current evidence and research. This reference discusses the benefits and challenges of building a mentoring relationship and highlights noteworthy topics such as mentoring minorities and women and mentoring to achieve change. The book's author is the recipient of the Leading Diversity Award from the National Cancer Institute. The book includes a foreword by Julie Thompson Klein who is a Professor of Humanities, English/Interdisciplinary Studies and Faculty Fellow in the Office for Teaching and Learning at Wayne State University in Detroit, Michigan. Dr. Klein is the past president of the Association for Integrative Studies (AIS) and former editor of the AIS journal, Issues in Integrative Studies. The goal of this book is to provide readers with a better understanding of the mentoring relationship and the overall process as it applies to the increasingly interdisciplinary field of science. Highlights mistaken beliefs about mentoring within a scientific environmentWritten in a conversational tone and supported by evidence-based researchFocuses on interdisciplinary mentoring in science and the modern dynamic of science and new scientific approaches to complex approachesIncludes note sections where readers can write down key topics or ideas from each chapter.
Includes bibliographical references and index.
Keywords: Mentoring in science; Electronic books